Advances in Nanofibers - Maguire, Russell (IntechOpen, 2013)
Book Advances in Nanofibers is a research publication that covers original research on developments within the Nanofibers field of study. The book is a collection of reviewed scholarly contributions written by different authors. Each scholarly contribution represents a chapter and each chapter is complete in itself but related to the major topics and objectives. The target audience comprises scholars and specialists in the field.